The Game Maker’s Companion: Game Development: The Journey Continues - Hagbood, Jacob (Apress, 2013)
Game Maker has become an extremely popular tool for beginners wanting to take their first steps into game development. This is hardly surprising, as its intuitive drag-and-drop programming system makes it very easy to start creating your own simple games. It’s also possible to make very professional-looking games using Game Maker, and you’ve probably already come across some impressive offerings made with it on the YoYo Games web site. Nonetheless, it’s not always easy for users to see how they can make that leap into creating more professional games for themselves—and that is exactly what this book is for.